2020
DOI: 10.1089/whr.2020.0029
|View full text |Cite|
|
Sign up to set email alerts
|

Sex Differences in Disease Profiles, Management, and Outcomes Among People with Atrial Fibrillation After Ischemic Stroke: Aggregated and Individual Participant Data Meta-Analyses

Abstract: Objectives: To examine sex differences in disease profiles, management, and survival at 1 and 5 years after ischemic stroke (IS) among people with atrial fibrillation (AF). Methods: We performed a systematic literature search of reports of AF at IS onset according to sex. We undertook an individual participant data meta-analysis (IPDMA) of nine population-based stroke incidence studies conducted in Australasia, Europe, and South America (1993-2014). Poisson regression was used to estimate women:men mortality r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 60 publications
2
4
0
Order By: Relevance
“…In line with our results, previous reports from other countries also indicated that women ischemic stroke patients had older age and a higher prevalence of hypertension, diabetes mellitus, and atrial fibrillation. 3,[20][21][22] Previous surveys or registry data from China also draw similar conclusions. 10,11,23 In addition, the administration of in-hospital treatments was comparable between women and men patients.…”
Section: Discussionsupporting
confidence: 66%
“…In line with our results, previous reports from other countries also indicated that women ischemic stroke patients had older age and a higher prevalence of hypertension, diabetes mellitus, and atrial fibrillation. 3,[20][21][22] Previous surveys or registry data from China also draw similar conclusions. 10,11,23 In addition, the administration of in-hospital treatments was comparable between women and men patients.…”
Section: Discussionsupporting
confidence: 66%
“… 135 Among patients with ischaemic stroke, females more often present with atrial fibrillation, hypertension, obesity and T2D than males. 136 , 137 …”
Section: Sex Differences In the Association Of Hypertension With Cvdmentioning
confidence: 99%
“…Prior findings from registry studies and meta-analyses across different countries showed that female ischemic stroke patients were older and a higher proportion had hypertension or atrial fibrillation. [6][7][8]10] A national survey in China reported that female stroke survivors had a significantly higher prevalence of hypertension, diabetes mellitus, and atrial fibrillation than male stroke survivors. [34] The INTERSTROKE case-control study consisting of participants from 32 countries in Asia, Africa, and the Middle East demonstrated using population-attributable risk that hypertension was the most impactful risk factor for stroke in women compared to men.…”
Section: In-hospital Outcomesmentioning
confidence: 99%
“…[1–5] Generally, while strokes are more common among men, several traditional cardiovascular risk factors (e.g., hypertension and atrial fibrillation) are more prevalent among women. [6–8] Women are also less likely to receive thrombolysis, more likely to be severely ill and more likely to have unfavorable outcomes. [9–12] With the recognition of sex disparities in health, American Heart Association's Go Red for Women Campaign was launched in the United States to close the gaps and eliminate disparities.…”
Section: Introductionmentioning
confidence: 99%